2021
DOI: 10.25078/jpm.v7i2.2349
|View full text |Cite
|
Sign up to set email alerts
|

Kepercayaan Dan Kepuasan Penggunaan LMS Mahasiswa Selama Pembelajaran Daring

Abstract: <em>The implementation of online learning through the Learning Management System (LMS) is universal in higher education. The presentation of learning at the LMS is expected to facilitate student learning during the Covid-19 pandemic. This aims of research to determine the effect of belief in the use of LMS on learning satisfaction in LMS carried out by students. The research approach uses a quantitative type of correlation. This study used a research sample of 101 students. The research instrument is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…The use of LMS in learning provides its own challenges (Rafi et al, 2020). The use of LMS in learning has been widely practiced in universities (Prasetyo et al, 2021). Furthermore, Ramdhan & Siregar (2023) revealed that nearly all participants expressed ease in learning and perceived the modules within LMS as more effective.…”
Section: Postest Resultsmentioning
confidence: 99%
“…The use of LMS in learning provides its own challenges (Rafi et al, 2020). The use of LMS in learning has been widely practiced in universities (Prasetyo et al, 2021). Furthermore, Ramdhan & Siregar (2023) revealed that nearly all participants expressed ease in learning and perceived the modules within LMS as more effective.…”
Section: Postest Resultsmentioning
confidence: 99%
“…Hal ini membuat interaksi guru dengan peserta didik dalam proses pembelajaran lebih interaktif sehingga suasana belajar menjadi menyenangkan. Pernyataan ini didukung oleh hasil penelitian Prasetyo et al (2021) dimana mahasiswa memberikan respon positif dan kepercayaan terhadap penggunaan LMS dalam pembelajaran. Hal ini dinilai dari segi kualitas materi, ketuntasan belajar, kemudahan penggunaan, dan aktivitas selama pembelajaran.…”
Section: Pembahasanunclassified
“…Online learning or often called Learning Management System (LMS) is an effort made by an educational institution to manage the design and implementation of learning systems, as well as evaluate the learning process and results electronically (Bradley, 2020;Y. Fitriani, 2020;Prasetyo et al, 2021;Rahman et al, 2019;Shurygin & Sabirova, 2017). The purpose of online learning is to fulfil educational standards by utilising information technology, which allows interaction between students and lecturers through computer devices or gadgets connected to the internet (Bovermann et al, 2018;Guo et al, 2018;Murcahyanto, 2023bMurcahyanto, , 2023a.…”
Section: Introductionmentioning
confidence: 99%